Blizzard of the blue moon - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2006)
The magic tree house carries Jack and Annie to New York City in 1938 on a mission to rescue the last unicorn.
"A Merlin Mission."
"A Stepping Stone Book."
Keywords: Time travel -- Fiction; Magic -- Fiction; Unicorns -- Fiction; Depressions -- 1929 -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction